Laboratory and in situ investigations of tracking cutters for computer-aided design of shearer drums - O. Z. Hekimoglu; M. Ayhan; B. Tiryaki (Canadian Institute of Mining, Metallurgy and Petroleum, 2003)
"This paper discusses the aspects of tracking cutters related to the computer-aided design of shearer drums. A comprehensive computer analysis of drum dynamic parameters for multi-tracking tool arrangement is not presently available, as the current computer programs mainly consider the aspects of single tracking. Despite the fact that the single-tracking arrangement is recommended for efficient cutting, some major drum manufacturers have been seen to persistently adhere to multi-tracking, probably due to a lack of information. Further studies in this field are believed to contribute greatly to the current understanding of the computer-aided design of shearer drums.A number of laboratory simulation trials and long-term underground investigations were carried out in detail on tracking cutter arrangement, and an equation required for a computer program was derived. The results obtained from computer assessment of dynamic parameters for drums with multi-tracking arrangement were found to be in accordance with those of the underground trials, indicating the validity of the equations. The procedure adopted for the computer appraisal of the shearer drums designed with a multi-tracking concept, as described in this study, is therefore recommended to be considered in the currently employed computer programs."